Wartość życia u podstaw islamskiej (bio)etyki - Marcin Leźnicki (Studia Ecologiae et Bioethicae)
The aim of this article is to present the position of Islamic ethics and bioethics on the issue of the value of life. To better illustrate this topic the article is divided into two parts. In the first, the authors provide an overview of ethics, and relate it Islamic bioethics, including its sources and inspirations, while in the second, the authors examine the value of life as depicted from the perspective of Quranic ethics and Islamic bioethics of both the Shi’a and the Sunnis. Although the text has a propedeutic character it is important because it adds another theological-philosophical layer to the complex bioethical discussion that lies at the heart of the current dispute about the value of human life.